Enhancing the Understanding of Resilience in Health Systems of Low- and Middle-income Countries: A Qualitative Evidence Synthesis - Pauline Yongeun Grimm; Sandy Oliver; Sonja Merten; Wai Wai Han; Kaspar Wyss (Kerman University of Medical Sciences, 2022)
BackgroundA country's health system faces pressure when hit by an unexpected shock, such as what we observe in the midst of the coronavirus disease 2019 (COVID-19) pandemic. The concept of resilience is highly relevant in this context and is a prerequisite for a health system capable of withstanding future shocks. By exploring how the key dimensions of the resilient health system framework are applied, the present systematic review synthesizes the vital features of resilient health systems in low- and middle-income countries. The aim of this review is to ascertain the relevance of health system resilience in the context of a major shock, through better understanding its dimensions, uses and implications. MethodsThe review uses the best-fit framework synthesis approach. An a priori conceptual framework was selected and a coding framework created. A systematic search identified 4284 unique citations from electronic databases and reports by non-governmental organisations, 12 of which met the inclusion criteria. Data were extracted and coded against the pre-existing themes. Themes outside of the a priori framework were collated to form a refined list of themes. Then, all twelve studies were revisited using the new list of themes in the context of each study. ResultsTen themes were generated from the analysis. Five confirmed the a priori conceptual framework that capture the dynamic attributes of a resilient system. Five new themes were identified as foundational for achieving resilience: realigned relationships, foresight and motivation as drivers, and emergency preparedness and change management as organisational mechanisms. ConclusionThe refined conceptual model shows how the themes inter-connect. The foundations of resilience appear to be critical especially in resource-constrained settings to unlock the dynamic attributes of resilience. This review prompts countries to consider building the foundations of resilience described here as a priority to better prepare for future shocks.